Lesões intestinais decorrentes de isquemia e reperfusão: Fisiopatologia e modelos experimentais - Ribeiro, Marcelo Eduardo [UNESP]; Yoshida, Winston Bonetti [UNESP] (My University, 2005)
The intestinal ischemia is unusual in vascular surgery emergency. Its main causes are embolisms and arterial thrombosis. In addition to severe ischemia, reperfusion of the ischemic tissues can lead to several complications that may worsen the ischemic lesion and produce a life threatening situation caused by systemic alterations. Intestinal tissue injuries due to ischemia and reperfusion have been demonstrated in clinical and experimental studies, in which pathophysiology and adequate treatment were also studied. The great variety of experimental models used and results achieved reflect the need for an intestinal ischemia and reperfusion experimental model that is simple, reproducible and consistent, in order to search for treatments that can reduce the damage caused by this situation. In this review, the main pathophysiologic aspects and the most used experimental models will be reviewed. Copyright © 2005 by Sociedade Brasileira de Angiologia e Cirurgia Vascular.
Reperfusion injury after intestinal ischemia: Pathophysiology and experimental models
Keywords: Intestines; Ischemia; Reperfusion; artery thrombosis; disease severity; embolism; experimental model; human; intestine injury; intestine ischemia; nonhuman; pathophysiology; reperfusion injury; review; vascular surgery